2012
DOI: 10.1007/s12035-012-8264-y
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 in Development and Diseases of the Central Nervous System

Abstract: High mobility group box 1 (HMGB1) is widely expressed in cells of vertebrates in two forms: a nuclear "architectural" factor and a secreted inflammatory factor. During early brain development, HMGB1 displays a complex temporal and spatial distribution pattern in the central nervous system. It facilitates neurite outgrowth and cell migration critical for processes, such as forebrain development. During adulthood, HMGB1 serves to induce neuroinflammation after injury, such as lesions in the spinal cord and brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(132 citation statements)
references
References 56 publications
1
130
0
1
Order By: Relevance
“…[27][28][29] There is growing evidence that HMGB1 and RAGE signaling and related inflammatory reactions are involved in the pathogenesis of various disorders, including cardiovascular, neurodegenerative, and immune disorders. 12,20,[30][31][32][33] We have recently established that plasma levels of HMGB1 as well as interactions between HMGB1 and RAGE were increased significantly after ischemic stroke onset both in human and mice. 14 We also found that administration of recombinant sRAGE effectively protects mice from ischemic reperfusion injury and protects primary neurons from energy deprivation-induced cell death via a mechanism involving reduced RAGE-associated inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] There is growing evidence that HMGB1 and RAGE signaling and related inflammatory reactions are involved in the pathogenesis of various disorders, including cardiovascular, neurodegenerative, and immune disorders. 12,20,[30][31][32][33] We have recently established that plasma levels of HMGB1 as well as interactions between HMGB1 and RAGE were increased significantly after ischemic stroke onset both in human and mice. 14 We also found that administration of recombinant sRAGE effectively protects mice from ischemic reperfusion injury and protects primary neurons from energy deprivation-induced cell death via a mechanism involving reduced RAGE-associated inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 has a pivotal role in the induction of neuroinflammatory processes in neurodegenerative conditions (Fang et al, 2012), cerebral ischemia (Yang et al, 2010), traumatic brain injury (Corps et al, 2015), seizure (Vezzani, 2014), and ethanolinduced neurotoxicity (Zou and Crews, 2014). HMGB1 is a DNA structural protein that has been co-opted by the innate immune system to signal damage during sterile inflammatory conditions (Bianchi, 2007).…”
Section: Hmgb1mentioning
confidence: 99%
“…HMGB1 also serves to induce neuroinflammation after injury, such as lesions in the spinal cord and brain (16,18,59). To elucidate whether neuron and microglia, a type of glial cells that are the resident macrophages of the brain and spinal cord, have participated in the physiological processes through activation of one or both HMGB1 paralog signalings, we first succeeded in preparation of the recombinant proteins by eukaryotic expression in 293T cells and then of the polyclonal antibodies (Fig.…”
Section: Differential Responses Of Ghmgb1a and Ghmgb1b To The Spinal mentioning
confidence: 99%
“…A plethora of studies have revealed that HMGB1 plays double-edged roles in neural development and neurodegeneration (59). Therefore, we transfected the plasmids of gHMGB1a and gHMGB1b into PC12 and SH-SY5Y cell lines to examine their effects on neurites.…”
Section: Differential Responses Of Ghmgb1a and Ghmgb1b To The Spinal mentioning
confidence: 99%